Adolescents' Increasing Stress Response to Social Evaluation: Pubertal Effects on Cortisol and Alpha‐Amylase During Public Speaking. Issue 1 (2nd May 2013) - van, Esther; de, Mark; Miers, Anne C.; Bokhorst, Caroline L.; Westenberg, P. Michiel
<x xml:space="preserve">Abstract</x> Stress responses to social evaluation are thought to increase during adolescence, which may be due to pubertal maturation. However, empirical evidence is scarce. This study is the first to investigate the relation between pubertal development and biological responses to a social‐evaluative stressor longitudinally. Participants performed the Leiden Public Speaking Task twice, with a 2‐year interval (N = 217; age at Time 1: 8–17 years). The results support an increase in sensitivity to social evaluation during adolescence. The overall cortisol and alpha‐amylase responses increased—both between and within participants—and were more strongly related to self‐reported pubertal development than to age. The cortisol response shifted from speech delivery toward anticipation. The alpha‐amylase response increased in both phases.